2020
DOI: 10.1007/s10640-020-00491-4
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposure and Covid-19 in Dutch Municipalities

Abstract: In light of the existing preliminary evidence of a link between Covid-19 and poor air quality, which is largely based upon correlations, we estimate the relationship between long term air pollution exposure and Covid-19 in 355 municipalities in the Netherlands. Using detailed data we find compelling evidence of a positive relationship between air pollution, and particularly PM 2.5 concentrations, and Covid-19 cases, hospital admissions and deaths. This relationship persists even after controlling for a wide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
166
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 25 publications
18
166
4
5
Order By: Relevance
“…Recent data from the USA indicate that the number of COVID-19 cases and fatalities experienced by Black citizens were higher (up to 75%) than in the rest of the population, although they constitute only a small proportion (32% at maximum) of the overall population [38]. Outside conventional epidemiology, comprehensive econometric methods were applied to study the effect of PM 2.5 and COVID-19 cases, hospitalisations and deaths in all 355 municipalities in the Netherlands [34]. The authors attempted a number of sensitivity analyses to account for unmeasured confounding (or omitted variable bias as commonly known in econometrics), measurement error in the exposure and the outcome and spatial spill-over.…”
Section: Air Pollution and Covid-19mentioning
confidence: 99%
“…Recent data from the USA indicate that the number of COVID-19 cases and fatalities experienced by Black citizens were higher (up to 75%) than in the rest of the population, although they constitute only a small proportion (32% at maximum) of the overall population [38]. Outside conventional epidemiology, comprehensive econometric methods were applied to study the effect of PM 2.5 and COVID-19 cases, hospitalisations and deaths in all 355 municipalities in the Netherlands [34]. The authors attempted a number of sensitivity analyses to account for unmeasured confounding (or omitted variable bias as commonly known in econometrics), measurement error in the exposure and the outcome and spatial spill-over.…”
Section: Air Pollution and Covid-19mentioning
confidence: 99%
“…IPLC’s rights need to be fully secured and their traditional knowledge preserved. [ 78 – 84 ] Food insecurity One in 3 women affected by anemia. Perpetuates poverty cycles.…”
Section: A Proposal For Human-rights and Gender-responsive One Healthmentioning
confidence: 99%
“…Patients from Black, Asian and Minority Ethnic (BAME) communities were found to account for 34% of critically ill COVID-19 patients nationally, despite constituting 14% of the UK’s population [ 82 ]. Overall deprivation was associated with worse coronavirus outcomes, and a more detailed examination of the living environment revealed that air pollution was also positively associated with an increase in COVID-19 cases and deaths, in the UK and the Netherlands [ 83 , 84 ]. Of concern are the repercussions that the COVID-19 pandemic has already had on access to sexual and reproductive health and rights, which are fundamental to people’s health and survival.…”
Section: A Proposal For Human-rights and Gender-responsive One Healthmentioning
confidence: 99%
“…Haze exposure during the prenatal period has been linked to decreased adult height attainment (Tan-Soo & Pattanayak, 2019), and short-term exposure during the severe 2015 fires is estimated to have caused 100,300 or more premature mortalities in Equatorial Asia (Koplitz et al, 2016; see also Crippa et al, 2016). This is important in light of recent reports that increased air pollution may elevate COVID-19 case numbers, hospital admissions and mortality (Cole, Ozgen & Strobl, 2020;Conticini, Frediani & Caro, 2020;Ogen, 2020;Wu et al, 2020), and has led to concerns being raised by both regional think tanks (Gan et al, 2020) and relevant experts in media reports regarding peatland fires and COVID-19 (Jong, 2020b;Listiyorini, 2020;Varkkey, 2020), though under COVID-19 lockdown conditions such impacts may be at least partially mitigated by general shutdowns of anthropogenic activities (Kanniah et al, 2020). In particular, in a pre-print article, Cole, Ozgen & Strobl (2020) and Wu et al (2020) report that an increase in PM2.5 (small particulate matter) of just 1 mg/m 3 is associated with a 8-16.6% increase in COVID-19 death rate, whereas in Central Kalimantan, PM2.5 levels have been reported to exceed 1,500 mg/m 3 during severe fire periods (Atwood et al, 2016), and average mean exposures between 2011 and 2015 have been estimated at 26 mg/m 3 , over double the recommended WHO exposure limit (Uda, Hein & Atmoko, 2019).…”
Section: Public Health and Potential Combined Impacts From Haze Pollumentioning
confidence: 99%